Gene Expression Regulation in Airway Pathogens: Importance for Otitis Media - Janoušková, Martina; Straw, Megan Laura; Su, Yu-Ching; Riesbeck, Kristian (Frontiers in Cellular and Infection Microbiology, 2022)
Otitis media (OM) is an inflammatory disorder in the middle ear. It is mainly caused by viruses or bacteria associated with the airways. Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis are the three main pathogens in infection-related OM, especially in younger children. In this review, we will focus upon the multifaceted gene regulation mechanisms that are well-orchestrated in S. pneumoniae, H. influenzae, and M. catarrhalis during the course of infection in the middle ear either in experimental OM or in clinical settings. The sophisticated findings from the past 10 years on how the othopathogens govern their virulence phenotypes for survival and host adaptation via phase variation- and quorum sensing-dependent gene regulation, will be systematically discussed. Comprehensive understanding of gene expression regulation mechanisms employed by pathogens during the onset of OM may provide new insights for the design of a new generation of antimicrobial agents in the fight against bacterial pathogens while combating the serious emergence of antimicrobial resistance.